Testing The Physical Properties of Various Onggok Balance with Tofu Making Liquid Waster as Alternative Feed Ingredients - Farisy, Daffa Al; Abun, Abun; Hernaman, Iman (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
Onggok is a by-product of tapioca flour processing which can be utilized by adding tofu making liquid waste. This study is to determine the difference and the best balance on physical properties, namely specific gravity, stack density, and stack compaction density. Carried out at the Laboratory of Animal Nutrition and Animal Feed Chemistry, Padjadjaran University. The study used an experimental method with a Complete Randomized Design (RAL) using five treatments and four repeats consisting of P0 (2 kg onggok: 0 liters of tofu liquid waste), P1 (2 kg ongdok: 2 liters of tofu liquid waste), P2 (2 kg onggok: 1 liter of tofu liquid waste), P3 (2 kg onggok: 700 ml of tofu liquid waste), and P4 (2 kg ongdok:  500 ml of tofu liquid waste). The results showed a noticeable effect (P<0.05) of physical properties testing. The P2 treatment produced the highest value in the specific gravity test of 1.111 g/mL, the P1 treatment produced the highest value in the pile density test of 0.237 g/mL, and the result of the stack compaction density in P1 of 0.282 g/mL. This study concluded that the addition of tofu making liquid waste can increase pile density and pile compaction density